Consumer Preferences and Attitudes towards Antibiotic Use in Food Animals - Katherine E. Adam; Ann Bruce (MDPI AG, 2023)
Antimicrobial resistance (AMR) is one of the major challenges faced by society, with the real threat of the failure of many medical procedures. Antibiotics are also used in livestock production and provide a potential pathway to increasing AMR. The central challenge involves ensuring animal health and welfare while securing the long-term effectiveness of antibiotics. This paper reports the results of a survey of 5693 respondents from the customer panels of four major UK supermarkets regarding preferences and attitudes towards antibiotic use in food animals, and their perspectives on how the balance between animal welfare and human benefit can be achieved. The results of these surveys are consistent with those from other countries that found that consumers generally have limited knowledge about antibiotic use in agriculture and AMR, with around 50% responding "don't know" to many questions. There was agreement about the benefits of antibiotics outweighing harm, with 40% agreeing that, overall, the use of antibiotics to treat disease in farm animals delivers more benefit than harm. However, 44% neither agreed nor disagreed, indicating a high level of uncertainty and a situation that is potentially unstable. The seriousness of the AMR challenge is such that continued action for the more discriminating use of antibiotics must continue.